CALCULATION OF SOIL DENSITY IN THE EARTH'S CRUST IN S++ PROGRAMMING LANGUAGE (Multidisciplinary Journal of Science and Technology, 2024)
Calculating soil density in civil engineering in C++ is an object-oriented programming and calculation when the problem has indicators.